BIOFERTILIZERS : BETTER APPROACH TOWARDS FORMING - JYOTI AGRAWAL (Innovare Journal of Agricultural Sciences, 2021)
In the present scenario, chemical fertilizers are seem to be a good source of inorganic nutrients to fulfill the need of increasing demand of crop production. Although, with respect to the time, so many adverse effects of chemical fertilizers on human health, natural microflora of soil and on the ecosystem have been reported which are not stoppable. On the other hand, in our nature, a great number of useful soil micro-organisms are found that can help plants to absorb nutrients. A bio-fertilizer is a substance which contains beneficial living microorganisms and used as a modernized form of organic fertilizer. From few decades, biofertlilizers are reported to exhibit similar beneficial and lesser harmful impacts on the ecosystem. So, as an alternative of chemical fertilizers, biofertlilizers are broadly used as a healthier and sustainable method for agriculture. In this review, we will discuss about the adverse effects of chemical fertilizers on different parts of environment in contrast to the benefits of biofertlilizers along with the brief history and mechanism of action of bacterial biofertlilizers.